Влияние малых концентраций полиэтиленгликолей-1500 и -4000 на механизмы диффузии молекул воды по данным нейтроноскопии - Кармазина, Т.В.; Слисенко, В.И.; Василькевич, А.А.; Базилюк, Т.Н.; Петрачков, А.А.; Омельченко, В.М. (Видавничий дім "Академперіодика" НАН України, 2008)
The characteristics of the dynamics of water molecules in the presence of PEG-1500 and -4000 are determined. The effect of relatively small concentrations lower than 2.0 mass. % of these PEG on the water dynamics and the mechanisms of its translation motions is analyzed. The data were obtained by the quasielastic slow neutron scattering method.